2018
DOI: 10.3390/su10103794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corporate Life Cycle on Corporate Social Responsibility: Evidence from Korea

Abstract: Few studies examine how firms make strategic decisions over time. In this study, we test whether a firm undertakes corporate social responsibility (CSR) activities as a function of its life-cycle stage. Drawing on prior CSR research that finds ethical concerns and opportunistic behavior to be two key motivations that underpin CSR activities, we hypothesize that firms in their growth stage are positively associated with CSR, while firms in stage of decline are less likely to invest in CSR. The empirical finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…Unlike the above research analyzing the US companies, Yao et al [2] reported that younger Chinese firms are likely to disclose CSR, indicating their stronger desire for the capital market. Similarly, Lee and Choi [9] used Korean samples and found that firms at the growth stage invest more in CSR. These contrasting evidences show that the relationship between corporate age and CSR is inconsistent and unclear.…”
Section: Prior Research On Corporate Age and Csrmentioning
confidence: 98%
See 3 more Smart Citations
“…Unlike the above research analyzing the US companies, Yao et al [2] reported that younger Chinese firms are likely to disclose CSR, indicating their stronger desire for the capital market. Similarly, Lee and Choi [9] used Korean samples and found that firms at the growth stage invest more in CSR. These contrasting evidences show that the relationship between corporate age and CSR is inconsistent and unclear.…”
Section: Prior Research On Corporate Age and Csrmentioning
confidence: 98%
“…This trait of Korean CSR may enable companies with a short listing period to engage in CSR activities to enhance firm value. Lee and Choi [9] increased this possibility by showing that in Korea, growth firms are likely to invest more in CSR than those in other life-cycle stages. In addition, CSR plays an important role in broadening a firm's shareholder base by attracting more institutional investors and increases stock liquidity [19].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the literature, we used CSR scores released by The Korea Economic Justice Institute (KEJI) as a proxy for CSP [33,34]. The KEJI annually evaluates Korean public companies in terms of social responsibility and ethical management and publicly provides CSP of the top 200 companies.…”
Section: Corporate Social Performance (Csp)mentioning
confidence: 99%